Emerging Roles of MicroRNAs in Diffuse Large B-Cell Lymphoma: From Molecular Mechanisms to Clinical Translation, Liquid Biopsy, and Precision Medicine - Corina Joldes; Laura Jimbu; Oana Mesaros; Madalina Onciul; Bogdan Fetica; Mihnea Zdrenghea (Biomedicines, 2026)
Diffuse large B-cell lymphoma (DLBCL), the most prevalent subtype of non-Hodgkin lymphoma (NHL), is an aggressive and fairly heterogeneous group with diverse clinical, pathological, and molecular features. Despite the success of first-line immunochemotherapy, relapsed or treatment-resistant forms remain a clinical challenge. Consequently, minimally invasive markers are needed to predict refractoriness. Recently, circulating microRNAs (miRNAs) have emerged as highly stable, promising biomarkers. MiRNAs such as miR-21, miR-155, miR-222-3p, and the miR-17~92 cluster act as oncogenes that promote tumor survival, while others, such as miR-34, miR-181a, miR-144, miR-101, miR-10a, and miR-320, act as tumor suppressors. Despite multiple recent publications that have correlated dysregulated miRNAs with diagnostic and prognostic importance, the clinical translation has not been fully addressed. Overall, this review provides an updated perspective on the potential of miRNAs in DLBCL and outlines key challenges and future directions for their integration into precision oncology, as miRNAs can remodel the clinical management of DLBCL by enabling earlier diagnosis, improved prognostication, and personalized treatment approaches.